The foundations of European Community law : an introduction to the constitutional and administrative law of the European Community - Hartley, Trevor C. (Oxford : Clarendon Press ; New York : Oxford University Press, 1994)
This is the third edition of Trevor Hartley's acclaimed introduction to the legal framework and institutions of the European Community. It has been completely rewritten and revised to take account of the major changes which have occurred since 1988. These include the establishment of the Court of First Instance and the coming into force of the Maastricht Treaty on European Union. In the course of updating the work Proffessor Hartley has analysed and discussed more than 150 new cases, emanating from the European Court of Justice and Court of First Instance, which have had a direct bearing upon the constitution and administrative arrangements of the European Union. Besides being a standard text for undergraduate law students studying EC law, it has also justly acquired a reputation among practitioners, for whom it remains an ideal source of reference as well as a lucid and perceptive introduction to the principle elements of Community law.
Note on Citation and Reporting of European Court Cases -- Table of Community Treaties -- Table of United Kingdom Statutes -- Pt. I. Community Institutions. Ch. 1. The Political Institutions. Ch. 2. The European Court and the Court of Auditors -- Pt. II. The Community Legal System. Ch. 3. Acts of the Member States. Ch. 4. Community Acts. Ch. 5. General Principles of Law. Ch. 6. Agreements with Third Countries -- Pt. III. Community Law and the Member States. Ch. 7. Direct Effect and the Supremacy of Community Law. Ch. 8. The National Reaction. Ch. 9. Preliminary References. Ch. 10. Enforcement Actions -- Pt. IV. Administrative Law. Ch. 11. Reviewable Acts. Ch. 12. Locus Standi. Ch. 13. Failure to Act. Ch. 14. Indirect Challenge. Ch. 15. Grounds of Review. Ch. 16. Annulment and Revocation. Ch. 17. Community Obligations.
Includes bibliographical references and index.
Keywords: Law -- European Economic Community countries